Robin's Wish and the Complex Causal Web of Death by Suicide. Issue 2 (3rd April 2023) - Joiner, Thomas E.; Robison, Morgan
Abstract: The documentary film Robin's Wish aims to reclaim the media scrutiny around Robin Williams' death, fixating on causation being solely attributed to a postmortem diagnosis of which Williams was unaware—Lewy Body Dementia. The film and other sources as well defined and animated the view that Williams' death by suicide was fully a result of this medical condition, dismissing any possible role for mental disorders. The need to distance from mental disorders can have a palpable undercurrent of stigmatization of them; the documentary missed the opportunity to make its point and simultaneously build allyship with others who have lost someone to suicide who were clearly battling a mental disorder. In this context, we emphasize the importance of looking at causation mediationally (e.g., a neurological condition triggering a major depressive episode culminating, in turn, in death by suicide). Only through encompassing all elements and complexities of the human spirit and condition can we appropriately pay tribute to those we have lost to suicide and simultaneously de-stigmatize mental disorders.